2017
DOI: 10.17129/botsci.850
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and seed yield in Tunisian castor bean (<em>Ricinus communis</em> L.)

Abstract: Background and hypothesis: Castor bean (Ricinus communis) is spontaneous in Tunisia with a wide geographical distribution. To study seed morphology we introduced J index as the percent of similarity of seed images to an ovoid. Reduced seed size, J index and color intensity were observed in the population grown in the desert (Martín Gómez et al. 2016). Our objective is to analyze the variability in castor bean grown from seeds obtained from different geographic origins, to describe morphotypes and to find pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although the shape of the seeds is conserved within a species (Cervantes & Martín‐Gómez, 2019), studies have reported that it can vary according to the edaphic and climatic characteristics of the region where the mother plant is grown. The effect of the growth environment on seed shape was found in Olea europaea L. (Hannachi et al., 2017) and Ricinus communis L. (Saadaoui et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although the shape of the seeds is conserved within a species (Cervantes & Martín‐Gómez, 2019), studies have reported that it can vary according to the edaphic and climatic characteristics of the region where the mother plant is grown. The effect of the growth environment on seed shape was found in Olea europaea L. (Hannachi et al., 2017) and Ricinus communis L. (Saadaoui et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Torke or Zebra for example), the latter being more rounded [25,26]. Also, seed shape may vary in plants grown in different geographic regions or climatic conditions, as observed in Olea europaea L. [27], Jatropha curcas L. [28], and Ricinus communis L. [29,30]. Finally, quantitative differences in seed shape between wild-type seeds and mutants have been also reported for Arabidopsis thaliana, Medicago truncatula, and Lotus japonicus [31][32][33].…”
Section: Variations In Seed Shapementioning
confidence: 98%
“…The cardioid was also the figure used in the model legume Lotus japonicus L. (Fabaceae) [33], and in Capparis spinosa L. (Capparaceae) [35]. The ellipse was the model in Jatropha curcas L. and Ricinus communis L. (Euphorbiaceae) [28][29][30], and in Quercus species (Fagaceae) [36].…”
Section: Variations In Seed Shapementioning
confidence: 99%
See 1 more Smart Citation
“…In Capparis spinosa L., the comparison of seed images with the cardioid curve was helpful to describe differences between two subspecies (Saadaoui et al, 2013). In the Euphorbiaceae Jatropha curcas L. and Ricinus communis L., seed shape was quantified by comparison with an ellipse; the form/production relationship has been verified (Saadaoui et al, 2015(Saadaoui et al, , 2017Martín-Gómez et al, 2016).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%